(untitled) (Journal of Fatima Jinnah Medical University, 2022)
Background: Prostatic cancer is highly ominous in men and survives hormonal insufficiency. We studied Androgen Receptor (AR) expression in various Gleason scores (GS) of prostatic adenocarcinoma by using immunohistochemistry. Materials and methods: This descriptive analytical study was carried out at King Edward Medical University/Mayo Hospital, Lahore in 2016. Slides were prepared from 60 paraffin blocks of prostatic adenocarcinoma and stained for evaluation of different parameters like Gleason score (GS), histopathological grades (well differentiated, intermediate or high grade) and AR immunohistochemistry score. Data entry and analysis was carried out using SPSS version 22. The relationship between different parameters was determined by Pearson chi-square test. A p-value of < 0.05 was considered statistically significant. Results: Out of 60 cases, 15 (25%) had intermediate and 45 (75%) had high grade tumors. AR was positive in 59 (98.33%) cases. Among the positive cases, 5 (8.33%) had +1 score, 25 (41.67%) has +2 and 29 (48.33%) had +3 score. A significant association of AR expression with GS and histological grades was found. Conclusion: AR positivity is significantly associated with Gleason Score and histological grading of prostate adenocarcinoma, hence it may prove a useful diagnostic and prognostic marker for carcinoma prostate.